Gastro-bronchial fistula due to gastric stump adenocarcinoma - Ruso Martínez, Luis; Praderi, Raúl (Cirugía del Uruguay, 1992)
The authors present the case of a 67 year old patient who 20 years earlier had undergone a Billroth II gastrectomy due to gastroduodenal u/cus and is admitted because of fever and purulent bronchorrhea. While making an esophagogastroduodenum study, the bronchial tree was filled, showing the presence of an ample gastrobronchial fistula. Fibrogastroscopy certified the existence of cancer of the gastric fundus fistulized through the diaphragm. The patient died in septic state before being operated on.